Analysis of Pavement Failure (Flexible Foundation): A Case Study of Bauchi-Kaduna - Abdulmajid, Ibrahim; Yau, Engr. Yusuf; Enabulele, Ewemade Cornelius (Darul Yasin Al Sys, 2024)
This research investigates the causes of pavement failures shortly after a rehabilitation activity along Bauchi-Kaduna Road (Magama-Gumau-RahamaRoad.). One of the principal objectives of this research effort was to identify sources of Moisture and other conditions that led to the early rutting problems observed. Improper tack coat or failure, permeable dense-graded layers, inadequate drainage, and possibly insufficient Compaction of dense-graded material were the likely root causes of the observed moisture damage and consequential rutting problems. The other principal objective was to evaluate design, construction, and materials requirements -that will minimize the risk of such failures for future rehabilitation projects so that guidelines could be developed for this process.